Diagnostic performance of amyloid A protein quantification in fat tissue of patients with clinical AA amyloidosis - DİRESKENELİ, RAFİ HANER (INFORMA HEALTHCARE, 2007)
Objective. Amyloid A protein quantification in fat tissue is a new immunochemical method for detecting AA amyloidosis, a rare but serious disease. The objective was to assess diagnostic performance in clinical AA amyloidosis. Methods. Abdominal subcutaneous fat tissue of patients with AA amyloidosis was studied at the start of an international clinical trial with eprodisate (NC-503; 1,3-propanedisulfonate; Kiacta (TM)), an antiamyloid compound. All patients had renal findings, i.e. proteinuria (>= 1 g/day) or reduced creatinine clearance (20-60 ml/min). Controls were patients with other types of amyloidosis and arthritic patients without amyloidosis. Amyloid A protein was quantified by ELISA using monoclonal antihuman serum amyloid A antibodies. Congo red stained slides were scored by light microscopy in a semiquantitative way (0 to 4+). Results. Ample fat tissue (>50 mg) was available for analysis in 154 of 183 patients with AA amyloidosis and in 354 controls. The sensitivity of amyloid A protein quantification for detection of AA amyloidosis (>11.6 ng/mg fat tissue) was 84% (95% CI: 77-89%) and specificity 99% (95% CI: 98-100%). Amyloid A protein quantification and semiquantitative Congo red scoring were concordant. Men had lower amyloid A protein values than women (p < 0.0001) and patients with familial Mediterranean fever had lower values than patients with arthritis (p < 0.001) or other inflammatory diseases (p < 0.01). Conclusions. Amyloid A protein quantification in fat tissue is a sensitive and specific method for detection of clinical AA amyloidosis. Advantages are independence from staining quality and observer experience, direct confirmation of amyloid AA type, and potential for quantitative monitoring of tissue amyloid over time.
Keywords: systemic AA amyloidosis; amyloid A protein; fat tissue; sensitivity; specificity; Congo red stain; ADIPOSE-TISSUE; RHEUMATOID-ARTHRITIS; SYSTEMIC AMYLOIDOSIS; ADIPOCYTES; BIOPSIES; ASPIRATE; OBESITY; SAA